Treaty with the Wyandot, 1818. - United States; Wyandot Tribe ([Getzville, New York] : William S. Hein & Company, 2020)
Articles of a treaty made and concluded, at St. Mary's, in the state of Ohio, between Lewis Cass, Commissioner of the United States, thereto specially authorized by the President of the United States, and the chiefs and warriors of the Wyandot tribe of Indians--
"Treaty Number: NAM000089."
Treaty date: 9/20/1818.
7 Stat. 180
2 Indian Affairs Laws and Treaties (1904) 164
Extracted from: United States. Public statutes at large of the United States of America. Boston : Charles C. Little and James Brown, 1845-1867.
Extracted from: United States. Indian affairs : laws and treaties / compiled and edited by Charles J. Kappler. Washington : Government Printing Office, 1903-1971.
Keywords: Wyandot Tribe -- Treaties; Wyandot Indians -- Government relations; Wyandot Indians -- Legal status, laws, etc; Indians of North America -- Treaties; Treaties